Pengaruh Promosi Member Card dan Media Sosial terhadap Loyalitas Pelanggan Kaku Food Cabang Borong Kota Makassar - Muh. Erlangga; Chalid Imran Musa; Muhammad Ichwan Musa; Zainal Ruma; Muhammad Ilham Wardhana Haeruddin (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This research aims to determine the influence of Member Card promotions and social media on customer loyalty at the Kaku Food Borong branch Makassar City. The data used in this research is primary data of 100 samples. This type of research is included in quantitative research. The population in this study were all consumers who had shopped at the Kaku Food Borong branch in Makassar City and had a Member Card. Data collection was carried out using documentation and survey methods using questionnaires. The data analysis technique uses SPSS Version 29 analysis. The results of this research show that the Member Card promotion has a partially positive and significant effect on the loyalty of Kaku Food customers the Borong branch in Makassar City, then social media has a partially positive and significant effect on the loyalty of Kaku Food customers at the Borong branch in Makassar City. Simultaneously, Member Card promotions and social media influence customer loyalty at the Kaku Food Borong branch in Makassar City.